2014
DOI: 10.1590/s0034-737x2014000200002
|View full text |Cite
|
Sign up to set email alerts
|

Influência da cama de frango e de espaçamentos entre plantas na produtividade agroeconômica de mandioquinha-salsa

Abstract: Influence of broiler manure application methods and spacing arrangement between plants on Peruvian carrot economic yieldPeruvian carrots is an excellent alternative for small and medium farmers, especially within the concepts of family farming. Thus the aim of this study was to evaluate the agricultural economic yield of this crop when managed under two plant spacing arrangements (20 and 25 cm between plants) and different application methods of dried broiler manure on the soil [surface-applied (10 t ha

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The best result obtained might be related to differences in nutrient contents in both residues (Table 1), because the broiler manure based on sawdust contained higher levels of zinc (Zn), manganese (Mn), iron (Fe), calcium (Ca), magnesium (Mg), and phosphorus (P), which may have been more available throughout the plant cycle because of lower C/N ratio. The results were consistent with the reports by Torales et al (2014), who observed the elevation in P, K, and Mg levels in soil after broiler manure application for the production of commercial arracacia roots.…”
Section: Resultssupporting
confidence: 93%
“…The best result obtained might be related to differences in nutrient contents in both residues (Table 1), because the broiler manure based on sawdust contained higher levels of zinc (Zn), manganese (Mn), iron (Fe), calcium (Ca), magnesium (Mg), and phosphorus (P), which may have been more available throughout the plant cycle because of lower C/N ratio. The results were consistent with the reports by Torales et al (2014), who observed the elevation in P, K, and Mg levels in soil after broiler manure application for the production of commercial arracacia roots.…”
Section: Resultssupporting
confidence: 93%
“…The production costs were calculated by adapting the tables for 'Comum' arrowroot plants presented by Abrão (2016), as well as those for 'Amarela de Carandaí' Peruvian carrots reported by Torales et al (2014) and Heid et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…The authors found no response regarding fresh mass of leaf and stem and concluded that species native to Cerrado are undemanding for fertilization. The positive response to organic fertilization in this study results from the different conditions of soil, climate, and others, it is, therefore, important to produce more leaf mass and consequently more secondary metabolites (Knapik et al, 2005;Torales et al, 2014;Trevizan et al, 2016).…”
Section: Discussionmentioning
confidence: 86%
“…In addition to intercropping, the use of organic waste as chicken manure, which is a primary source of nutrients, can contribute to reduce reliance on agricultural inputs, as well as to provide a sustainable destination for these materials (Torales et al, 2014;Rogeri et al, 2015). Organic manure can increase medicinal plant production by promoting slow and gradual release of nutrients to the soil over time and improving physical, chemical, and biological attributes of the soil such as reduction of soil density, increase in soil porosity, and increase in soil-water retention (Costa et al, 2009), increase in cation exchange capacity, increase levels of P, K, Ca, Mg, Cu and Zn (Rogeri et al, 2015), and increase soil microbial respiration (Andrade et al, 2015).…”
Section: Introductionmentioning
confidence: 99%